Marisa Mori and the Futurists a woman artist in an age of fascism - Griffiths, Jennifer S. (Bloomsbury Visual Arts, 2023)
This book introduces a compelling new personality to the modernist canon, Marisa Mori (1900-1985), who became the only female contributor to The Futurist Cookbook (1932) with her recipe for "Italian Breasts in the Sun." Providing something more complex than a traditional biographical account, Griffiths presents a feminist critique of Mori's art, converging on issues of gender, culture, and history to offer new critical perspectives on Italian modernism. If subsequently written out of modernist memory, Mori was once at the center of the Futurism movement in Italy; yet she worked outside the major European capitals and fluctuated between traditional figurative subjects and abstract experimentation. As a result, her in-between pictures can help to re-think the margins of modernism. By situating Mori's most significant artworks in the critical context of interwar Fascism, and highlighting her artistic contributions before, during, and after her Futurist decade, Griffiths contributes to a growing body of knowledge on the women who participated in the Italian Futurist movement. In doing so, she explores a woman artist's struggle for modernity among the Italian Futurists in an age of Fascism.
Keywords: Mori, Marisa -- 1900-1985; Geschlechterrolle; Faschismus; Künstlerin; Feminismus; Futurismus; Mori, Marisa / 1900-1985; Art / Futurist / Italy / 20th century / Criticism; Gender studies / Feminism; Women artists